2023
DOI: 10.1242/jeb.244862
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining control: metabolism of molting Arctic seals in water and when hauled out

Abstract: Seals haul out of water for extended periods during the annual molt, when they shed and regrow their pelage. This behavior is believed to limit heat loss to the environment given increased peripheral blood flow to support tissue regeneration. The degree to which time in water, particularly during the molt, may affect thermoregulatory costs is poorly understood. We measured the resting metabolism of three spotted (Phoca largha), one ringed (Pusa hispida), and one bearded (Erignathus barbatus) seal during and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…Avoiding cold water would limit energy expenditure and blubber depletion, while a faster molt would limit fasting duration and extend the next foraging period 72 , resulting in higher at-sea body condition, survival, and reproductive success 37 , 38 . Previous studies on ringed and spotted seals did not report supplementary energy expenditure at sea 16 , and our data did not show any difference in body mass loss between at-sea and on-land females. This highlights that the physiological cost of molting, i.e., for tissue regeneration, may be greater than the cost of heat loss in cold water.…”
Section: Resultscontrasting
confidence: 67%
See 3 more Smart Citations
“…Avoiding cold water would limit energy expenditure and blubber depletion, while a faster molt would limit fasting duration and extend the next foraging period 72 , resulting in higher at-sea body condition, survival, and reproductive success 37 , 38 . Previous studies on ringed and spotted seals did not report supplementary energy expenditure at sea 16 , and our data did not show any difference in body mass loss between at-sea and on-land females. This highlights that the physiological cost of molting, i.e., for tissue regeneration, may be greater than the cost of heat loss in cold water.…”
Section: Resultscontrasting
confidence: 67%
“…Surprisingly, females that went to sea did not lose more body mass than females remaining on land but had higher stomach temperatures, which could reflect a higher metabolic rate, hence higher energy loss at sea. However, previous studies on molting Arctic seals (ringed Pusa hispida , spotted Phoca largha , and bearded seals Erignathus barbatus ) reported that metabolic rates were similar when resting in air and water 16 . An increase in stomach temperature might be detected at the onset of diving as a result of heat generated by muscles during swimming 73 , which questions the reliability of STP to estimate metabolic variation.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations